Analisis Pengetahuan dan Perilaku Masyarakat terhadap Penerapan Protokol Kesehatan Pencegahan Covid-19 di Kelurahan Pringrejo Kota Pekalongan - Ana Setyowati; Putri Andanawarih (Jurnal Kebidanan Harapan Ibu Pekalongan, 2023)
Coronavirus or commonly referred to as Covid-19 has been spreading throughout the world for almost 1 year which is a new type of virus that has never been previously identified in humans. The health protocol to prevent the spread of Covid-19 was established by WHO and the Indonesian Ministry of Health, namely 3M (washing hands, wearing masks and maintaining distance). This protocol has become a guideline in preventing the spread of Covid-19 and has been socialized to the wider community. This is done by the government as an effort to break the chain of the spread of Covid-19, so it is necessary to have understanding and knowledge of the entire community. Knowledge is also the most important domain in the formation of behavior. The purpose of this study was to analyze the relationship between knowledge and behavior of the Pringrejo Village community towards the implementation of health protocols in preventing Covid-19. This research was conducted using an analytic observational study with a cross sectional research design. The sampling technique used purposive sampling. The instrument used used an observation sheet and the analysis used the Chi Square statistical test. The results showed that there was a significant relationship between knowledge and community behavior towards the implementation of the covid 19 prevention health protocol with a p value of 0.00 (<0.05). Good behavior in question is covid 19 prevention behavior including washing hands either with soap or hand sanitazer, wearing a mask when leaving the house, maintaining a minimum distance of 1 meter, avoiding crowds, doing social distancing and bathing and changing clothes after traveling.